ANALISIS LIKUIDITAS, SOLVABILITAS, DAN MAKRO EKONOMI TERHADAP KEPUTUSAN INVESTASI (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Jody, Setiawan; Pristiana, Ulfi (Jurnal Manajemen, 2023)
The purpose of this study was to known the effect of liquidity, leverage, and macro economic on investment decision. This research was conducted on manufacture campany pharmaceutical sub-sector who registered on stock exchange period 2019-2021. Total amount of samples thas used to this research was 10 companies with purposive sampling method. The analysis technique used by multiple linear regression analysis. The result of this research has shown that simultaneous liquidity, leverage, and macro economic had significant effect on investment decision. While in partial variable liquidity was not affected sognificant on investment decision, variable leverage had significant effect on invesment decision, and macro economic variable was not affected on investment decision.